Determinants Influencing Business Financing (Capital Structure) in The Selected Industry - Tambahani, Gabriel Justin; Brabenec, Tomáš; Jablonský, Petr; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2026)
In this thesis, I examine whether Sharia compliance in Indonesia and Malaysia impacts the capital structure of non-financial firms in chosen industries. To test this, the thesis used OLS regression with a sample of 500 publicly-listed companies across the Food & Beverages, Information Technology, and Industrial Goods sectors in Indonesia and Malaysia. In Indonesia, Sharia-compliance is associated with lower leverage, consistent with the hypothesis, that Sharia-compliance may become a constraint for compliant firms. On the other hand, Malaysia results show that Sharia compliance is not connected with lower leverage, which suggests that a mature Islamic finance ecosystem may allow Sharia-compliant firms to substitute toward alternative Islamic instruments without lowering overall leverage. The findings show that the effect of Sharia-compliance on overall capital structure is not universal, depending on the maturity of the Islamic finance market.
Vedoucí práce: Tomáš Brabenec
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor bakal. práce]; bakalářské práce; bachelor's theses